Tertiary Lymphoid Structures in Cancer: The Double-Edged Sword Role in Antitumor Immunity and Potential Therapeutic Induction Strategies - Kang, Wendi; Feng, Zhichao; Luo, Jianwei; He, Zhenhu; Liu, Jun; Wu, Jianzhen; Rong, Pengfei (Frontiers in Immunology, 2021)
The complex tumor microenvironment (TME) plays a vital role in cancer development and dramatically determines the efficacy of immunotherapy. Tertiary lymphoid structures (TLSs) within the TME are well recognized and consist of T cell-rich areas containing dendritic cells (DCs) and B cell-rich areas containing germinal centers (GCs). Accumulating research has indicated that there is a close association between tumor-associated TLSs and favorable clinical outcomes in most types of cancers, though a minority of studies have reported an association between TLSs and a poor prognosis. Overall, the double-edged sword role of TLSs in the TME and potential mechanisms need to be further investigated, which will provide novel therapeutic perspectives for antitumor immunoregulation. In this review, we focus on discussing the main functions of TLSs in the TME and recent advances in the therapeutic manipulation of TLSs through multiple strategies to enhance local antitumor immunity.